Non-technological innovation: current issues and perspectives - Pereira, Cristina (2012)
Innovation can be considered to be a complex phenomenon including technical and non-technical aspects. A remarkable increase in the interdisciplinary attention devoted to innovation has been noticed over the recent decades but the formal technological and economic aspects of innovation have received much more attention and have been taken into account in a far greater number of analyses, despite the great importance of the non-technological dimension of innovation. Non-technological innovation is an important element of firms’ innovation activities that both supplement and complement technological innovation. Some scholars have point out that innovation in firms is not just about developing and applying new technologies but also to adopt and re-organize business routines, internal organization, external relations and marketing. And other authors maintain that the innovation management literature stresses the importance of integrating product, process and organizational innovation for successfully transferring new ideas and new business opportunities into market success and emphasizing the crucial role of linking R&D, technological innovation and new marketing approaches. This paper attempts a review on the important subject of non-technological innovation. The main ideas on the non-technological dimension of innovation research will be highlighted, followed by an attempt to integrate diverse and disparate perspectives on the subject, to present evidence on possible generalizations and to discuss eventual research gaps and opportunities for further studies. The relationship between technological and non-technological innovation is complex and not fully understood. Among several aspects that will be covered in this paper, two specific ones will receive special attention in this brief analysis: the evidence on the impacts of non-technological innovation, and the measurements efforts that have been made concerning this phenomenon.